Adjustment to trade opening: The case of labor share in India's manufacturing industry - Prachi Gupta; Matthias Helble (Asian Development Bank Institute (ADBI), 2018)
The objective of this paper is to study how manufacturing plants in India adjusted to trade liberalization during the period 1998-99 to 2007-08. We estimate how the labor share changed due to tariff reduction. Our results indicate that a decline in output tariffs led to an increase in the labor share of income. In contrast, a fall in input tariffs led to a decrease in the labor share. Controlling for factor intensity, we find that in technology intensive and human capital resource intensive sectors, both a decline in input and output tariff rates led to a decline in labor share. A fall in tariffs only led to an increase in labor share for labor intensive and low-technology plants. Hence, India's bias towards capital and technology intensive production explains the overall decline in labor share in the post reform period. Furthermore, the empirical results show that labor adjustment occurred more efficiently in Indian states with flexible labor laws.
Keywords: F13; F16; F66; L60; 330; trade reforms; labor share; India; manufacturing